Challenges And Strategies Of Carbon Accounting Treatment In The Coal Mining Sector: An Empirical Study In East Kalimantan - Saputra, Handayani Jaka; Maulidiah, Rahma (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The coal mining sector is facing increasing global pressure due to heightened awareness of climate change and growing demands for sustainable business practices. The decline in mining company stock values reflects escalating reputational and financial risks, compelling companies to preserve corporate value through strategies that align with green economic principles. This study aims to evaluate the treatment of carbon accounting as a component of environmental accounting within the context of coal mining, particularly in East Kalimantan. The research focuses on the recording, measurement, presentation, and disclosure of carbon emissions in financial statements, based on the Indonesian Financial Accounting Standards (PSAK) and international standards such as ISO 14064 and the GHG Protocol. Furthermore, this study analyzes the impact of carbon emission calculations and carbon sequestration offset capacity on corporate financial ratios, using a quantitative approach to estimate both lost and generated carbon emissions from production activities. The findings draw upon prior research that emphasizes the importance of integrating environmental information into financial reporting to enhance corporate transparency and competitiveness. Consequently, this study contributes to the formulation of relevant and applicable carbon accounting strategies for the mining sector, while addressing the implementation challenges within Indonesia’s regulatory and business frameworks.